Effectiveness of Phytobiotic Supplementation as a Feed Additive - Ardiansyah, Widiastuti; Tusaban, Tusaban; Achmad, Dewi Shinta (Journal La Lifesci, 2025)
The rearing of Mojosari ducks in Indonesia has become increasingly important as an alternative source of animal protein. However, the high cholesterol content in duck meat presents a challenge to its consumption. This study aims to evaluate the effect of turmeric supplementation in feed on cholesterol levels in the liver, blood, and meat of Mojosari ducks, as well as the organoleptic quality of the resulting meat. The experiment utilized a factorial Randomized Completely Block Design (RCBD), where ducks were divided into four treatment groups based on turmeric dosage: 0%, 6%, 8%, and 10%. Parameters measured included cholesterol levels in the liver, blood, and meat, as well as organoleptic assessments of taste, aroma, texture, color, and tenderness of the meat. The results indicated that turmeric supplementation significantly reduced cholesterol levels in the liver, blood, and meat of the ducks, with the 8% and 10% turmeric groups showing the lowest cholesterol levels. Turmeric supplementation also improved the tenderness and color quality of the duck meat, although no significant differences were observed in taste and aroma. The reduction in cholesterol levels suggests the potential of turmeric as an effective feed additive for producing healthier duck meat that is more appealing to consumers. These findings have implications for the development of feed based on natural ingredients that can enhance duck meat quality and support the sustainability of the duck farming industry in Indonesia.